Politics and Consumer Prices in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
The motivations of the Arab Spring that have marked the history of humanity over the last few months have left political economists, researchers, governments and international policymakers pondering over how the quality of political institutions affect consumer welfare in terms of commodity prices. This paper investigates the effects of political establishments on consumer prices in the African continent. Findings suggest that in comparison with authoritarian regimes, democracies better provide for institutions that keep inflationary pressures on commodity prices in check. As a policy implication, improving the quality of democratic institutions will ameliorate consumer welfare through lower inflation rates. Such government quality institutional determinants include, among others: voice and accountability, rule of law, regulation quality, control of corruption and press freedom.
Keywords: I30; O00; P00; Q00; P50; 330; Consumer prices; Political institutions; Welfare; Africa